OPTIMALISASI KEMANDIRIAN LANSIA DALAM MELAKUKAN ACTIVITY DAILY LIVING (ADL) MELALUI PEMBERDAYAAN PENDAMPING LANSIA - Rahayu, Dian Yuniar Syanti; Usman, Reni Devianti; Putri, Dwi Purnama (Poltekkes Kemenkes Mataram, 2024)
The elderly are an important part of society that often faces challenges in carrying out daily activities due to factors such as physical, health, and environmental changes. Seniors often face challenges in carrying out activities of daily living (ADLs) due to physical and cognitive changes associated with aging. Efforts to increase their independence in ADLs are an important need in order to promote an optimal quality of life in old age, a holistic approach involving social support, changes to an elderly-friendly environment, and education for families and caregivers are also very important. Community service aims to increase the independence of the elderly in daily activities (ADLs) through various interventions that involve the active participation of cadres and families through education and training The results of this service show that actively involving the elderly in the process of planning and implementing programs can increase the sense of belonging and effectiveness of interventions. Social support from the community also plays an important role in promoting the independence of the elderly, this is shown by an increase in the knowledge of elderly companions before and after education and demonstration, the calculated t value is greater than the t table with p 0.05 which is 0.000, it can be concluded that there is a significant difference from the knowledge of elderly companions before and after education. The findings and experiences of this service make a valuable contribution to broader efforts in building an elderly-friendly society and promoting the holistic well-being of the elderly. The implementation of collaborative and inclusive strategies in community service is an important step towards an empowered and caring society for the elderly population.